PENGHITUNGAN, PENYETORAN DAN PELAPORAN PPH 21 SEBAGAI PERTANGGUNGJAWABAN KEWAJIBAN PERPAJAKAN PADA PERUSAHAAN OUTSOURCING PT PUSTEKINDO SOLUSITAMA DI TANGERANG SELATAN - Santioso, Linda; Marcello; Gunawan, Nita Patricia (Jurnal Serina Abdimas, 2024)
Companies providing labor (outsourcing) play a significant role in export-oriented company activities. Export companies often use production processes based on orders from customers. In an uncertain world economy and a global crisis as a result of the Covid-19 pandemic and war between countries, companies do not dare to immediately accept permanent employees. An alternative to meeting labor needs, companies use outsourcing of labor, through companies that operate in the field of labor providers. The salary system for permanent employees and outsourced employees is the same, namely in accordance with the Provincial Minimum Wage (UMP), if any, incentives, position allowances, etc. will be added. With the increase in the UMP in 2023, the wages earned by the Company's permanent employees (calculated by the company internally) and outsourced employees (should be calculated by the company providing the workforce) are already above Non-Taxable Income (PTKP) meaning they have to pay income tax article 21 (PPh 21 ) on wages, allowances, THR and other income. The problem is that companies providing labor have never calculated, deducted, deposited and reported taxes on their employees. In accordance with the holding system implemented in Indonesia, every company that provides income above the PTKP must withhold tax on its employees' income. The solution to avoid problems in the tax sector is that the company must carry out its obligations with a holding system, by carrying out calculations, deductions and reporting correctly on the income of all its employees in accordance with the applicable tax regulations. The resulting output is that the Company receives guidelines or methods for calculating and withholding taxes, so that employees who previously did not understand this policy become aware. These calculations and deductions can be implemented in all companies that use outsourced labor. Apart from that, to prevent tax bills or tax audits from arising. The method used is through counseling, training and mentoring starting from calculations, deposits (E_billing), tax reporting (E_filing).